2023
DOI: 10.1002/cbdv.202300793
|View full text |Cite
|
Sign up to set email alerts
|

Species Differentiation and Quality Evaluation for Atractylodes Medicinal Plants by GC/MS Coupled with Chemometric Analysis

Zicheng Ma,
Guoqiang Liu,
Zijie Yang
et al.

Abstract: The utilization of rhizomes from the genus Atractylodes has been challenging due to their closely related origins. In this study, we developed an analytical strategy to differentiate Atractylodes lancea (A. lancea), Atractylodes chinensis (A. chinensis), Atractylodes japonica (A. japonica), and Atractylodes macrocephala (A. macrocephala), and compared their volatile compositions. Gas chromatography‐mass spectrometry (GC/MS) was used to analyze the volatile profiles of essential oils extracted from 59 batches o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 29 publications
0
3
0
Order By: Relevance
“…Zhang et al [44] identified atramacronoids A-C (18)(19)(20) from the rhizomes of A. macrocephala using spectroscopic data analysis, chemical calculations, and X-ray diffraction, which were found to contain an unusual 6/6/5/5/6 skeleton furnished by an unexpected C-8-C-16 linkage. Subsequently, twenty undescribed eudesmane-type sesquiterpenes named atramacronoids D-W (21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35)(36)(37)(38)(39)(40) were identified in the rhizomes of A. macrocephala using extensive spectroscopic data analysis, Snatzke's rule, ECD calculations, and X-ray crystallographic analysis [45,46]. A chemical investigation of the ethanol extract of A. lancea resulted in the isolation of nine eudesmanetype sesquiterpenoids (41)(42)(43)(44)(45)(46)(47)(48)(49), and their structures were elucidated using spectroscopic techniques and HRESIMS [47].…”
Section: Eudesmane-type Sesquiterpenesmentioning
confidence: 99%
See 1 more Smart Citation
“…Zhang et al [44] identified atramacronoids A-C (18)(19)(20) from the rhizomes of A. macrocephala using spectroscopic data analysis, chemical calculations, and X-ray diffraction, which were found to contain an unusual 6/6/5/5/6 skeleton furnished by an unexpected C-8-C-16 linkage. Subsequently, twenty undescribed eudesmane-type sesquiterpenes named atramacronoids D-W (21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35)(36)(37)(38)(39)(40) were identified in the rhizomes of A. macrocephala using extensive spectroscopic data analysis, Snatzke's rule, ECD calculations, and X-ray crystallographic analysis [45,46]. A chemical investigation of the ethanol extract of A. lancea resulted in the isolation of nine eudesmanetype sesquiterpenoids (41)(42)(43)(44)(45)(46)(47)(48)(49), and their structures were elucidated using spectroscopic techniques and HRESIMS [47].…”
Section: Eudesmane-type Sesquiterpenesmentioning
confidence: 99%
“…β -eudesmol, atractylon, and hinesol are usually used as chemical markers for evaluating the quality of Atractylodes DC. in different regions [ 22 , 23 , 24 , 25 ]. Many studies have been conducted on Atractylodes DC.…”
Section: Introductionmentioning
confidence: 99%
“…A. chinensis has been traditionally used to treat digestive disorders, rheumatic diseases, and visual disorders [4]. The main active constituents of A. chinensis are atractylodin, atractylon, and β-eudesmol [5]. Modern pharmacological studies have shown that these substances have excellent pharmacological properties, such as anti-inflammatory, anticancer, anti-tumor, hypoglycemic, and neuroprotective [2,[6][7][8].…”
Section: Introductionmentioning
confidence: 99%